DeepWPD: A deep learning based wavelet packet decomposition to remove Moiré pattern from screen capture images. - Khan, Ibrahim (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.